The Power of Optical/IR Interferometry: Recent Scientific Results and 2nd Generation Instrumentation: Proceedings of the ESO Workshop held in Garching, Germany, 4 - 8 April 2005 - Richichi, Andrea (Eso Astrophysics Symposia, European Southern Observatory, 2008)
Celebrating the completion of the first phase of VLTI development, the ESO workshop The Power of Optical/IR Interferometry, held in 2005, gathered researchers together to review and discuss not just interferometers, but also how science uses interferometers and their impact on astronomy as a whole. This volume contains the proceedings of this workshop, serving as a reference for astronomers working with optical and infrared interferometry.